Виконайте дії, використовуючи формули скороченного множення:

1) (b+√c)(b-√c)

2) (√x-√y)(√x+√y)

3) (√15-2)(2+√15)

4) (1+3√2)(3√2-1)

5) (5√3-√11)(√11+5√3)

6) (a+√b)²

7) (√x-√y)²

8) (√3-√6)²

9) (1-2√3)²

10) (3√5+2√10)²

2

Ответы и объяснения

2013-06-22T09:21:52+00:00

1)(b+√c)(b-√c)=b^2-c

2) (√x-√y)(√x+√y)= x-y

3) (√15-2)(2+√15)= 15-4=11

4) (1+3√2)(3√2-1) = 18-1=17

5) (5√3-√11)(√11+5√3) = 75-11=64

6) (a+√b)² = a^2 +2a*b^1/2+ b

7) (√x-√y)² x-2√x√y +y

8) (√3-√6)² = 3 - 2*3*√2 +6 = 9-6√2

9) (1-2√3)²  = 1-4*√3 + 12= 13-4√3

10) (3√5+2√10)² = 45 + 12 * 5*√2 + 40 = 85 + 60√2

Лучший Ответ!
  • Участник Знаний
2013-06-22T09:22:53+00:00

1) (b+√c)(b-√c) = b² -√c²=b² -c

2) (√x-√y)(√x+√y)= √x² - √y² = x - y

3) (√15-2)(2+√15)= (√15)² -2² = 15 -4 = 11

4) (1+3√2)(3√2-1) (3√2)² - 1² =  18 - 1= 17

5) (5√3-√11)(√11+5√3)=(5√3)² - (√11)² = 75 - 11 =64

6) (a+√b)² = a² + 2a√b +b

7) (√x-√y)² = x - 2√(xy) +y

8) (√3-√6)² = 3 - 2 √(3· 6) + 6 = 9 -√18 =9 - 3√2

9) (1-2√3)² = 1 - 2·1·2√3 +(2√3)² = 1 - 4√3 + 12 = 13 - 4√3

10) (3√5+2√10)²= (3√5)²+ 2·3√5·2√10+(2√10)² =45 + 60√2 +40 = 85 + 60√2